Art applied Inside Outside/Petra Blaisse - Blaisse, Petra 1955- (MACK, 2024)
This retrospective of the oeuvre of Petra Blaisse and her acclaimed studio Inside Outside presents a kaleidoscopic view of their work across interior, exhibition, and landscape design over the course of more than three decades. Rather than working solely on static buildings, Inside Outside design environments across a huge variety of scales, from expansive urban landscapes to intimate domestic spaces defined by soft textile walls. The resulting spaces defy conventional classification. This comprehensive survey encompasses renowned projects including the recently completed Taipei Performing Arts Center; the Kunsthal Rotterdam; Biblioteca degli Alberi in Milan, a park spanning almost ten hectares; and LocHal Library in Tilburg, a vast factory repurposed using an architecture of semi-translucent curtains. It also presents revelatory unrealised projects and explores the studio’s many collaborations, including the rich body of work produced with OMA since the late 1980s. Opening with a collection of incisive thematic essays, this volume presents detailed accounts of projects from 1985 to the present day, accompanied by personal accounts by Petra Blaisse, partners Jana Crepon and Aura Luz Melis, and members of their team. The studio’s diverse methods and distinctive forms of expression are reflected in the book itself, whose language spans cartoonish production manuals, technical drawings, collage, photography, and scientific plant studies, over almost 900 pages. Art Applied suggests countless means of intervention and inhabitation, encouraging us to strive restlessly for new ways of seeing our built environment. Edited and introduced by Fredi Fischli and Niels Olsen, with newly commissioned texts by Penelope Curtis, Christophe Girot, Rem Koolhaas, Charlotte Matter, Fatma Al Sehlawi, Jack Self, Laurent Stalder, Helen Thomas, and Philip Ursprung
Monographie, die auf die Ausstellung "Inside Outside / Petra Blaisse: A Retrospective", vom 10. Oktober 2018 bis 14. Dezember 2018, ETH Zürich, Zentrum, Haupthalle, zurückgeht
Keywords: Blaisse, Petra -- 1955-; Inside Outside; Geschichte 1985-2023; Bildband